The effectiveness of HRM in managing employees and implementing change management strategies of Sheltech Engineering Limited - Islam, Md Raisul (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2021.